Evaluation of pyrite/sodium hypochlorite for activating purification of arsenic from fractured-bedrock groundwater - Da-won Lee; Ahn, Yongtae; Dong-Wan Cho; Bikram Basak; Byong-Hun Jeon; Choi, Jae Young (Pergamon Press Ltd., 2023)
In this work, the effectiveness of pyrite/sodium hypochlorite (FeS2/NaClO) treatment to eliminate arsenic (As) from fractured-bedrock groundwater via oxidative adsorption was evaluated. The As concentration in the tested reactors decreased sharply during the initial 5 min, as the addition of NaClO effectively increased the As removal efficiency, attaining 98.6% removal within 60 min in the presence of 0.05 M NaClO. There was no coexisting anion effect (Cl-, CO3-, HCO3-, NO3-, and F-) on the As removal capacity of FeS2/NaClO, except for the PO43- which resulted in less removal of As. X-ray spectroscopy analysis of As(III)-sorbed FeS2 surfaces revealed that a portion of As(III) was oxidized into As(V) during the adsorption process. Scanning electron microscopy-energydispersive spectrometer results of FeS2 exhibited the distribution of adsorbed As on the newly formed iron (oxy) hydroxide surfaces, with an As element ratio of 1.27%. A continuous flow-bed column study further demonstrated the efficiency of FeS2/NaClO treatment to lower the contamination level of As at the removal rates of 0.66-3.02 mg/L.day for 160 h. These results suggest that FeS2/NaClO treatment can be considered an effective strategy for removing As in groundwater of bedrock aquifers.